Preparation of porous silica nanocomposites from montmorillonite using sol-gel approach - Doroshenko, Dmytro; Pylypenko, Igor; Kornilovych, Borys; Subbota, Irina (Technology audit and production reserves, 2018)
The object of research is montmorillonite, which due to its properties and structure shows high sorption characteristics. However, the significant barrier to its use in industrial water purification technologies is the tendency of montmorillonite to be self-dispersed in aqueous solutions on elementary structural layers and to form stable suspensions. It creates difficulties with separating the solid and liquid phases after the sorption process. The authors used the sol-gel method for the synthesis of nanocomposite materials based on montmorillonite using tetraethoxysilane as a gelling agent. The synthesis involves the hydrolysis reaction of tetraethoxysilane and the subsequent polycondensation of silica molecules with hydroxyl groups of montmorillonite. The obtained samples inherit good sorption properties from a layered mineral and a solid frame structure from silica. Such a structure of synthesized nanocomposites is ensured by the presence of siloxane bonds, which help to bound together the elementary particles of montmorillonite. This, in turn, improves the water resistance of samples. Based on the results of rheological studies, it has been shown that the basic processes of the structure formation in the initial water-alcohol suspensions of the hydrolysis products of tetraethoxysilane and montmorillonite occur at a concentration of 1 % silica, which is due to the colloidal and chemical properties of the investigated systems. It has been shown that the treatment of montmorillonite with tetraethoxysilane hydrolysis products leads to the formation of a material with lower ability to swell and with better separation of liquid and solid phases. The optimum content of silica in the sample, which is in the range of 0.1 to 14 %, makes it possible to reduce the optical density of solutions by 2.5 times compared with the original montmorillonite. It has been shown that the synthesized materials retain a sufficiently high sorption capacity to remove the cationic dye methylene blue (up to 158 mg/g), which rises with increasing clay mineral content. And has been having a higher selectivity (up to 3.4 dm3/mg).